2020
DOI: 10.1016/j.fertnstert.2019.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive intentions in childless female adolescent and young adult cancer survivors

Abstract: Objective: To examine the association between prior cancer treatments, medical comorbidities, and voluntary childlessness in reproductive-aged women who are survivors of cancers diagnosed as adolescents and young adults (AYA survivors).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…The results of this study are contrary to of those a study conducted by Young et al (2019), which showed that more than half (74.8%) of survivors did not want to give birth after a cancer diagnosis and 98.5% did not want to adopt (Young et al, 2019). Survivors aged 36-40 years are three times more likely to be voluntarily childless than those aged 25-35 years (Lam et al, 2020). Not wanting to become pregnant can be caused by a possibly poor pregnancy outcome.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study are contrary to of those a study conducted by Young et al (2019), which showed that more than half (74.8%) of survivors did not want to give birth after a cancer diagnosis and 98.5% did not want to adopt (Young et al, 2019). Survivors aged 36-40 years are three times more likely to be voluntarily childless than those aged 25-35 years (Lam et al, 2020). Not wanting to become pregnant can be caused by a possibly poor pregnancy outcome.…”
Section: Discussioncontrasting
confidence: 99%
“…Age, sexual identity, history of pregnancy, cancer treatment were not significantly related to voluntarily childless (OR=0.60; 95% CI 0.35-1.02). Adolescent and young adult cancer survivors ages 36-40 years were three times more voluntarily childless than those aged 25-35 years (OR=2.97; 95% CI 1.71-5.18) (Lam et al, 2020). The results of a study by Mattsson et al (2020) showed that 59.6% of ovarian cancer survivors and 60% of uterine cancer survivors did not have children before being diagnosed with cancer.…”
Section: Psychosocial Impacts Affecting Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of reasons that may influence women’s choice to have a pregnancy or achieve a certain family size after cancer may be more important than biologic reproductive function for several survivors ( 24 , 47 ). A recent survey indicated that 21% of young women cancer survivors (mean age, 31.8 years) were voluntarily childless ( 25 ), and this was independent of diagnosis and medical comorbidities. Others, however, have found a similar desire to have children among cancer survivors compared with their siblings ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are additionally several other factors that influence the likelihood of pregnancy after cancer, including effects on rates of cohabitation/marriage, sexuality, and the impact of other long-term health consequences (generally termed “late effects”) of cancer treatment ( 18 , 19 , 20 , 21 , 22 , 23 ). Concerns regarding health status and disease recurrence may also be significant in decisions regarding family building after treatment ( 24 ); others may be voluntarily childless ( 25 ). Thus, there is a complex interplay of biologic, psychologic and social factors that determine postcancer fertility ( 26 ).…”
mentioning
confidence: 99%